Knowledge Management, Innovation, Technology and Direct Marketing as Antecedents of Data Mining: The Mediating Role of Direct Marketing in Saudi Banking Sector - Saeed, Tariq (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of the present research was to examine the relationship among innovation, technology, knowledge management, direct marketing, and data mining. Additionally, the present study also examined the mediating impact of direct marketing in present research. For data collection, questionnaires were distributed among the employees of banks in KSA. The response rate of usable questionnaires was 73%. The PLS-SEM technique was adopted to analyse the collected data. The data analysis showed that knowledge management, technology, and innovation significantly impact direct marketing. Moreover, data mining by banks also has a direct impact through direct marketing. In the end, direct marketing significantly mediates among knowledge management, innovation, technology, and data mining. Thus, all the proposed hypotheses are supported by the findings of the study. The present study fills the gap in the application of data mining to the strategic level of the banking sector. Moreover, the findings of the study are important for the policymakers and academicians of the banking sector in KSA.